Addressing the security needs of adolescent girls in protracted crises: Inclusive, responsive, and effective?. Issue 1 (2nd January 2021) - Gordon, Eleanor; Lee-Koo, Katrina
ABSTRACT: Adolescent girls face significant and often unique forms of insecurity in protracted crises. Yet, their specific needs tend to be overlooked by international agencies, and they are rarely consulted as programs are developed and implemented. Drawing from field research conducted in four crisis contexts—Lake Chad (Niger, Nigeria, and Cameroon), South Sudan and Uganda, Lebanon (Beirut), and Bangladesh (Cox's Bazar)—this article explores the experiences of insecurity that adolescent girls face in crisis contexts, and the extent to which responses to their needs are inclusive, responsive, and effective. Employing literature from inclusive peacebuilding, the article argues that marginalizing adolescent girls in the development and implementation of programs compromises the ability for such programs to be responsive to their needs. Moreover, it misses the opportunity to employ their skills, knowledge, and strengths to build resilience and security within their communities.